Synthesis and receptor dependent 4D-QSAR studies of 4, 5-dihydro-1, 3, 4-oxadiazole derivatives targeting cannabinoid receptor. Issue 3 (4th March 2021) - Hu, Z.H.; Zhao, T.S.; Liu, H.Y.; Lin, Q.X.; Tu, G.G.; Yang, B.W.
ABSTRACT: Cannabinoid receptor has been shown to be overexpressed in various types of cancers, especially non-small cell lung cancer. As a result, it could be used as novel target for anticancer treatments. Because receptor-dependent 4D-QSAR generates conformational ensemble profiles of compounds by molecular dynamics simulations at the binding site of the enzyme, this work describes the synthesis, biological activity evaluation and 4D-QSAR studies of 4, 5-dihydro-1, 3, 4-oxadiazole derivatives targeting cannabinoid receptor. Compared with WIN55, 212–2, compound 5 f showed the best antiproliferative activity. The receptor-dependent 4D-QSAR model was generated by multiple linear regression method using QSARINS. Leave- n -out cross-validation and chemical applicability domain were performed to analyse the independent test set and to verify the robustness of the model. The best 4D-QSAR model showed the following statistics: r 2  = 0.8487, Q 2 LOO  = 0.7667, Q 2 LNO  = 0.7524, and r 2 Pred  = 0.8358.